Lecture at crossroads in medical education: Is it time to say goodbye or introduce specific strategies to enhance their effectiveness? - Shrivastava, Saurabh; Shrivastava, Prateek (Current Medical Issues, 2022)
Over the past couple of decades, medical education has transformed extensively and a number of curricular reforms have been introduced. Lectures have been regarded as one of the teaching-learning methods, which have been with us for decades together, and have been adopted as one of the key strategies by the teachers to pass knowledge to students. In general, an effective lecture should aim to attain three goals, namely to impart useful information, introduce some kind of curiosity among students so that they decide about learning on their own, and provide practical relevance. Even though the lecture is being widely used, owing to their inherent limitations, their use as a solitary method of teaching-learning has been discouraged by the educators and regulatory bodies. To conclude, the lecture method in medical education has its own pros and cons. However, considering the advantages attributed to lectures and the presence of strategies that can be incorporated to eliminate the pitfalls in lectures, at present, lecture methods can be still continued for medical education delivery. Nevertheless, we have to make the lecture sessions interactive and ensure that students indulge in active learning, and this essentially calls for faculty development programs.